Promoting Differentiated Competencies Among RN-to-Bachelor of Science in Nursing Program Graduates. - McEwen, Melanie (Journal of Nursing Education, 2015)
Background: Bolstered by the Institute of Medicine's employment goal of 80% of baccalaureate (BSN)-prepared RNs by 2020, the number of RN-to-BSN programs has grown dramatically. This rapid growth has led to concerns about lack of standardization and significant variability in requirements related to content and expected competencies. Method:The Differentiated Essential Competencies (DECs) of Graduates of Texas Nursing Programs was reviewed to tease out the concepts, content, and competencies that are BSN-level specific and thereby appropriate for RN-to-BSN programs. Results: The current review was a compilation of differentiated competencies based on education level. In this article, numerous examples are drawn from the DECs and are organized by the major content areas common to RN-to-BSN programs. Conclusion: Faculty should examine the DECs to consider how they may be used to enhance RN-to-BSN programs, to evaluate their congruence with traditional BSN programs, and to ensure that program graduates are educationally prepared for practice in today's complex health care system. [Faculty should examine the DECs to consider how they may be used to enhance RN-to-BSN programs, to evaluate their congruence with traditional BSN programs, and to ensure that program graduates are educationally prepared for practice in today's complex health care system. [J Nurs Educ. 2015;54(11):615--623.]